Sisi Etika dan Profesionalisme Auditor Internal dari Sudut Pandang Tokoh Pewayangan Prabu Kresna - Diana, Nurian Afin; Hopung, Yoanelita Maria (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study focuses on optimizing the role of internal auditors by drawing inspiration from the character of Kresna in traditional wayang performances. The research employs a qualitative descriptive method, relying on primary data gathered through interviews with an internal auditor who has over 10 years of experience within an organization. The study explores perspectives and insights on decision-making in dilemmas, considering the principles and roles of internal auditors inspired by Kresna's characteristics. Consequently, internal auditors are encouraged to emulate Kresna's traits when making the best possible decisions in challenging situations, thereby enhancing their effectiveness and wisdom in fulfilling their responsibilities.